A cohort study on long-term exposure to air pollution and incidence of liver cirrhosis - Orioli, Riccardo (Environ Epidemiol, 2020)
Cirrhosis is an advanced liver disease affecting millions of people worldwide, involving high healthcare costs. Despite experimental evidence suggesting a possible role of airborne pollutants in liver diseases, epidemiological studies are lacking. We aimed at investigating the association between exposure to air pollutants and incidence of cirrhosis in a large population-based cohort in Rome. METHODS: We used an administrative cohort established from the 2001 census. We included all adults of 30 years of age or older who were free of cirrhosis, resulting in a study population of over 1.2 million subjects. Follow-up of the subjects ended on 31 December 2015. We ascertained incident cases of cirrhosis from regional mortality and hospital discharge registries using a validated algorithm. We assessed exposure of the subjects to PM(10), PM coarse, PM(2.5), PM(2.5) absorbance, NO(2), NOx, and PM metal components at their residential address using Land Use Regression models. We used Cox regression models, adjusted for relevant covariates, to estimate the association between air pollution exposure and cirrhosis incidence. RESULTS: We observed 10,111 incident cases of cirrhosis, with a crude incidence rate of 67 × 100,000 person-years. Long-term exposure to all pollutants tested was significantly associated with cirrhosis, e.g., PM(10) (hazard ratios [HR], 1.05; 95% confidence interval [CI], 1.01–1.09, per 10 µg/m(3) increments), PM coarse (HR, 1.11; 95% CI, 1.05–1.17, per 10 µg/m(3) increments), PM(2.5) (HR, 1.08; 95% CI, 1.03–1.13, per 5 µg/m(3) increments), and NO(2) (HR, 1.03; 95% CI, 1.02–1.05, per 10 µg/m(3) increments). The associations were robust in secondary analyses. CONCLUSIONS: Our findings suggest a possible contribution of air pollution to the development of cirrhosis.